2020
DOI: 10.1038/s41598-020-73707-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of heat on wheat dormancy, late maturity α-amylase and grain size under controlled conditions in diverse germplasm

Abstract: In the Australian wheat belts, short episodes of high temperatures or hot spells during grain filling are becoming increasingly common and have an enormous impact on yield and quality, bringing multi-billion losses annually. This problem will become recurrent under the climate change scenario that forecast increasing extreme temperatures, but so far, no systematic analysis of the resistance to hot spells has yet been performed in a diverse genetic background. We developed a protocol to study the effects of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The cool temperatures that induced LMA in WA8124 were like those that induced LMA in Australian and U.K. germplasm (Mrva and Mares, 2001, 2002; Farrell and Kettlewell, 2008). Previous studies reported heat-induced LMA in a U.K. variety and in 14 isolates from a collection of landraces (Farrell and Kettlewell, 2008; Barrero et al, 2020). Interestingly, a high temperature shock of 32°C day/25°C night, as well as temperature conditions that matched those used in the Farrell and Kettlewell (2008) study, failed to induce LMA in WA8124 (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…The cool temperatures that induced LMA in WA8124 were like those that induced LMA in Australian and U.K. germplasm (Mrva and Mares, 2001, 2002; Farrell and Kettlewell, 2008). Previous studies reported heat-induced LMA in a U.K. variety and in 14 isolates from a collection of landraces (Farrell and Kettlewell, 2008; Barrero et al, 2020). Interestingly, a high temperature shock of 32°C day/25°C night, as well as temperature conditions that matched those used in the Farrell and Kettlewell (2008) study, failed to induce LMA in WA8124 (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…1), suggesting that cold treatment enhances a general tendency towards elevated grain α-amylase activity. LMA can also be induced by a high temperature treatment during late grain maturation (Farrell and Kettlewell, 2008; Barrero et al, 2020). Differences in sensitivity to high and low temperature enhancement of LMA may also provide clues as to whether LMA is governed by multiple genetic mechanisms (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Buyers purchase grain with an FN below 300 s at a discounted price because a low FN is associated with a higher risk of poor end-use quality, including cakes that fall and sticky noodles or bread. In addition to preharvest sprouting, elevated α-amylase can result from genetic susceptibility to late maturity α-amylase (LMA), the induction of α-amylase by cool or high temperatures during late grain maturation (Derkx and Mares, 2020; Barrero et al, 2020). LMA is sometimes considered a defect in late grain development because α-amylase is produced during grain filling, a time in development when α-amylase levels are usually low and when the endosperm is accumulating rather than breaking down starch (Barrero et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During sprouting, these degradative processes decrease the quality of wheat flour when used to make breads, cakes, noodles, and other cereal-based products (Olaerts and Courtin 2018). LMA leads to the production of high isoelectric point (high pI) α-amylases in the aleurone as a result of a temperature shock during mid-grain development or prolonged cold throughout grain development (Mares and Mrva 2008;Barrero et al 2013Barrero et al , 2020Derkx and Mares 2020). During LMA, α-Amylase1 (α-Amy1) genes are expressed, resulting in the synthesis of enzymes that are retained in the grain until harvest and lead to unacceptably low FN (Mrva and Mares 1999;Barrero et al 2013;Cheng et al 2014;Mieog et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies focused on the underlying genetic, biochemical, and physiological mechanisms that lead to LMA have increased (Kondhare et al 2012(Kondhare et al , 2013(Kondhare et al , 2014Barrero et al 2013Barrero et al , 2020Cheng et al 2014;Derkx and Mares 2020;Derkx et al 2021;Liu et al 2021). Collectively, LMA studies have shown that this condition is a consequence of genotype, environment, and grain developmental stage (Mares and Mrva 2014;Derkx and Mares 2020;Derkx et al 2021).…”
Section: Introductionmentioning
confidence: 99%